Irradiation embrittlement and creep in fuel cladding and core components proceedings of the conference organized by the British Nuclear Energy Society in London, 9-10 November 1972 - Davis, Joyce Shirley (British Nuclear Energy Society, 1973)
Proceedings of a conference held on 9-10 November 1972.